THE STRATEGY OF COLLECTING ZAKAT, INFAQ, AND SHODAQOH FUNDS FROM ORPHANAGE INSTITUTIONS IN URBAN MUSLIM COMMUNITIES IN BANDAR LAMPUNG - Mubasit, Mubasit; Rosidi, Rosidi; Gandhi, Aryo; Nasuha, Ahmad Failasuf; Ambarwati, Diana (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
The research was motivated by the reduced interest of the Muzakki in channeling funds, both zakat, infaq, and shodaqoh, at the Amil Zakat Institution. Therefore, a good fundraising strategy is needed at the Amil Zakat Institution to increase interest and channeling of zakat funds by Muzakki, so that the objectives of the Amil Zakat Institution are achieved. The collection of Zakat, Infaq, and Shodaqoh (ZIS) funds is one of the important aspects of Islamic wealth management. The purpose of this research is to analyze the effective ZIS collection strategy at Amil Zakat Institution. This type of research is field research with a qualitative approach, with a case study method at one of the Amil Zakat Institutions (LAZ) at Rumah Yatim in the Bandar Lampung Region. The data collection method uses observation, interview, and documentation. This data was analyzed with an inductive approach to draw general conclusions from the specific data collected. The results showed that effective ZIS fundraising strategies include: Increasing public awareness through campaigns and education related to zakat; Optimizing the use of information technology, such as mobile applications, websites and social media; Partnership with government agencies and private companies in the management of professional zakat and corporate zakat; Improving services and ease of ZIS payment; Strengthening human resources and collection infrastructure. From this study, Amil Zakat institutions must design innovative and adaptive ZIS fund collection strategies in line with current developments to maximize the potential of ZIS funds for the welfare of the community.